Tackling post harvest loss in Ghana: Cost-effectiveness of technologies - Baral, Siddhartha; Hoffmann, Vivian (International Food Policy Research Institute, 2018)
Postharvest Loss (PHL) refers to measurable quality and quantity loss of food in the postharvest system. The postharvest system consists of inter-connected stages, from the act of harvest, to crop processing, storage, marketing and transportation, to the stage of consumption. PHL can occur at any stage in the postharvest chain. This note describes common types of PHL, approaches to mitigation, and the cost-effectiveness of technologies to achieve this. We begin with a section on common causes of loss, best practices for preventing these, and barriers to adoption of these practices. We then discuss prevention of loss during storage, for which several technological solutions have been developed and evaluated. Finally, we summarize the evidence on the cost-effectiveness of three such technologies that have been scientifically evaluated: hermetic storage bags, metal silos, and a cooling chamber